Screening of weed-competitive variety of transplant aman rice, its optimum nitrogen dose and plant spacing for effective weed management - S.M. Rezaul Karim; Golam Mohammad Faruk; M. A. Hakim (2014)
Two experiments were conducted at the Bangladesh Agricultural University, Mymensingh to screen